2017
DOI: 10.1038/s41598-017-14863-2
|View full text |Cite
|
Sign up to set email alerts
|

Drift-dependent changes in iceberg size-frequency distributions

Abstract: Although the size-frequency distributions of icebergs can provide insight into how they disintegrate, our understanding of this process is incomplete. Fundamentally, there is a discrepancy between iceberg power-law size-frequency distributions observed at glacial calving fronts and lognormal size-frequency distributions observed globally within open waters that remains unexplained. Here we use passive seismic monitoring to examine mechanisms of iceberg disintegration as a function of drift. Our results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 55 publications
2
42
3
Order By: Relevance
“…In contrast, Kirkham et al (2017) and Tournadre et al (2012) found that the size-frequency distribution of smaller icebergs located further from glacier calving sites was better represented by a log-normal model. .…”
Section: 1029/2018jc014388mentioning
confidence: 89%
See 4 more Smart Citations
“…In contrast, Kirkham et al (2017) and Tournadre et al (2012) found that the size-frequency distribution of smaller icebergs located further from glacier calving sites was better represented by a log-normal model. .…”
Section: 1029/2018jc014388mentioning
confidence: 89%
“…The mean slope of the power law distributions that were fit to the temporal and spatial snapshots in our study is very close to that reported for the size‐frequency distribution of Antarctic ice islands (−1.5; Bouhier et al, ; Tournadre et al, ). This suggests that ice islands in both the Arctic and the Antarctic deteriorate through a complex set of fracture and fragmentation mechanisms and that these deterioration processes occur similarly across a range of ice island sizes (Kirkham et al, ; Tournadre et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations